Librarian Co-Authored Systematic Reviews are Associated with Lower Risk of Bias Compared to Systematic Reviews with Acknowledgement of Librarians or No Participation by Librarians - Aamodt, Mikaela; Huurdeman, Hugo; Strømme, Hilde (Evidence Based Library and Information Practice, 2019)
Objective - To explore the prevalence of systematic reviews (SRs) and librarians’ involvement in them, and to investigate whether librarian co-authorship of SRs was associated with lower risk of bias.Methods - SRs by researchers at University of Oslo or Oslo University Hospital were counted and categorized by extent of librarian involvement and assessed for risk of bias using the tool Risk of Bias in Systematic Reviews (ROBIS).Results - Of 2,737 identified reviews, 324 (11.84%) were SRs as defined by the review authors. Of the 324 SRs, 4 (1.23%) had librarian co-authors, in 85 (26.23%) librarians were acknowledged or mentioned in the methods section. In the remaining 235 SRs (72.53%), there was no clear evidence that a librarian had been involved. Librarian co-authored SRs were associated with lower risk of bias compared to SRs with acknowledgement or no participation by librarians.Conclusion - SRs constitute a small portion of published reviews. Librarians rarely co-author SRs and are only acknowledged or mentioned in a quarter of our sample. The quality and documentation of literature searches in SRs remains a challenge. To minimise the risk of bias in SRs, librarians should advocate for co-authorship.